SOMATIC AND PSYCHOLOGICAL COMPLICATIONS OF OBESITY IN THE PEDIATRIC POPULATION : CONTEMPORARY CHALLENGES FOR CLINICAL PRACTICE – A SYSTEMATIC REVIEW - Idalia Myszor,; Michał Madej,; Maria Kubacka,; Lucjan Kocemba,; Gabriela Mroczka,; Sylwia Nycz-Jucha,; Paulina Łobaza,; Brygida Pinkowicz,; Piotr Rachwał,; Barbara Nowak-Misiąg, (International Journal of Innovative Technologies in Social Science, 2025)
Obesity in children is a pandemic of the 21st century. It is a clinically significant problem and one of the most alarming health issues observed in children worldwide. Overweight and obesity result from the interaction of environmental, genetic, iatrogenic and endocrine factors, and their consequences significantly affect overall quality of life. Over the past few decades, it has been shown that obesity in young people influences the future development of diseases such as metabolic, respiratory, cardiovascular, endocrine and psychosocial disorders. This article focuses on the consequences of obesity in children and adolescents, including hypertension, obstructive sleep apnoea, insulin resistance, type 2 diabetes, dyslipidaemia, NAFLD, endocrine disturbances such as premature puberty or PCOS, and a range of mental health issues. We summarise the most important short- and long-term effects of obesity in children and adolescents and highlight the importance of early diagnosis and a multidisciplinary therapeutic approach to prevent short- and long-term complications.